Distressed Migrant Population under Climate Change: A Survey of Climate Poverty in Three Chinese Megacities - Zhen LI; Qian LIU; Tongzhen YANG (Chinese Journal of Urban and Environmental Studies)
Urban areas are at high risk of climate change. The impact of extreme weather caused by climate change on different social groups is drawing increasing concerns. This paper focuses on the urban distressed migrant population who is marginalized in terms of society, economy and region. Social survey methods such as questionnaires, focus groups, and case interviews are used to collect data. Supported by the Beijing Social Work Development Center for Facilitators, a non-governmental social work organization, and their network branches in three Chinese megacities, a survey of climate change impacts and adaptation needs was carried out in areas with high concentrations of migrant population. On the basis of the study, this paper gives the connotation and identification criteria of the “distressed migrant population”, and analyzes the concrete influence of climate change, especially the extreme weather, on this population and their families. The survey shows that the frequent occurrence of extreme weather further exacerbates the survival pressure on the distressed migrant population, plunging them into a “climate poverty” trap, and creating urgent needs for adaptation, which are mainly manifested in two aspects: The first is a strong desire to reduce their living distress and climate vulnerability, including improving the living environment, health status, career development ability; the second is a strong desire to improve their resilience, including access to climate information, psychological stress relief, and social support. This paper concludes with policy implications on how to improve the adaptive capacity of the distressed migrant population from three aspects: material demand, community support and self-empowerment. This paper intends to raise attention to urban climate poverty groups and promote policy support.